Development of a Molecularly Imprinted Poly(Acrylic Acid)‐MWCNT Nanocomposite Electrochemical Sensor for Tramadol Determination in Pharmaceutical Samples. Issue 5 (30th January 2020) - Ricardo Teixeira Tarley, César; de Cássia Mendonça, Jhessica; Rianne da Rocha, Luana; Boareto Capelari, Tainara; Carolyne Prete, Maiyara; Cecílio Fonseca, Matheus; Midori de Oliveira, Fernanda; César Pereira, Arnaldo; Luiz Scheel, Guilherme; Bastos Borges, Keyller; Gava Segatelli, Mariana
Abstract: A new voltammetric sensor based on molecularly imprinted poly(acrylic acid)‐MWCNT nanocomposite (MIP‐MWCNT) drop‐coated onto glassy carbon electrode (GCE) was developed and applied to tramadol (TR) determination in pharmaceutical samples. The voltammetric sensor prepared by suspension of MIP‐MWCNT at 1 : 1 (w/w) ratio show an improved performance compared to unmodified GCE. The electrochemical method is based on preconcentration of tramadol onto MIP‐MWCNT modified GCE surface at −1.5 V vs Ag/AgCl for 180 s in 0.1 Britton‐Robinson buffer (pH 8.0) at stirred solution. Upon preconcentration, the differential anodic voltammogram was recorded under the optimized condition giving rise to an analytical curve varying from 9.0 up to 30.0 μmol L −1 (R 2 =0.997) and limits of detection and quantification of 1.4 and 4.8 μmol L −1, respectively. The method precision was assessed in terms of intraday (n=6) and interday (two consecutive days) precision, giving relative standard deviations (RSD%) values between 2.8 to 7.4 %. Excipients usually found in pharmaceutical pills (magnesium stearate, microcrystalline cellulose, starch, and silica) and paracetamol were evaluated as potential interferents, however no interference was evidenced in TR determination. The method applicability was evaluated by TR analysis in pharmaceutical samples. Moreover, the method accuracy was attested by comparison of addition and recovery assays with a reference technique (high‐performance liquid chromatography). Abstract :